2010
DOI: 10.1124/mol.110.065920
|View full text |Cite
|
Sign up to set email alerts
|

Different N-Terminal Motifs Determine Plasma Membrane Targeting of the Human Concentrative Nucleoside Transporter 3 in Polarized and Nonpolarized Cells

Abstract: Human concentrative nucleoside transporter 3 (hCNT3) is a broad-selectivity, high-affinity protein implicated in the uptake of most nucleoside-derived anticancer and antiviral drugs. Regulated trafficking of hCNT3 has been recently postulated as a suitable way to improve nucleoside-based therapies. Moreover, the recent identification of a putative novel hCNT3-type transporter lacking the first 69 amino acids and retained at the endoplasmic reticulum anticipated that the N terminus of hCNT3 contains critical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Previous studies in our laboratory suggested that sorting signals implicated in the membrane insertion of CNTs are localized in the intracellular N-terminal tail of these proteins [13,16,26]. This is based on the evidence that an alternative splicing variant of hCNT3, which is truncated in its N-terminus tail is retained in the ER [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in our laboratory suggested that sorting signals implicated in the membrane insertion of CNTs are localized in the intracellular N-terminal tail of these proteins [13,16,26]. This is based on the evidence that an alternative splicing variant of hCNT3, which is truncated in its N-terminus tail is retained in the ER [16].…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the evidence that an alternative splicing variant of hCNT3, which is truncated in its N-terminus tail is retained in the ER [16]. Moreover, a β-turn domain in this segment of the hCNT3 protein has been shown to be essential for proper sorting of the transporter to the apical plasma membrane in polarized epithelia [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the Val 57 -Thr 58 -Val 59 tripeptide at the N terminus of human concentrative nucleoside transporter 3 (hCNT3) appears to be the core of the endoplasmic reticulum export signal (47). Our preceding results have demonstrated that the 23 VRAETEL 29 aa residues require TRPC4 expression at the cell surface.…”
Section: Candidates For Regulators Of Trpc4 Channel Trafficking-mentioning
confidence: 97%
“…MDCK cells were plated on 12 mm diameter, 0.3 μm pore Transwell plates (Corning Incorporated, Corning, NY, USA) and transfected as described previously (Errasti‐Murugarren et al ., ). Proper expression and insertion of transporter proteins at the plasma membrane has been verified using YFP‐tagged transporters, as previously reported (Errasti‐Murugarren et al ., ; 2010a,b), and transport assays, as detailed below, using model substrates of hCNT‐ and hOCT‐type proteins (uridine and cytidine for hCNT1 and hCNT3, and MPP + for hOCT1). Uptake rates were determined as a control of transporter expression levels at the plasma membrane.…”
Section: Methodsmentioning
confidence: 97%